2007
DOI: 10.1016/j.febslet.2007.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine‐1‐phosphate induces the association of membrane‐type 1 matrix metalloproteinase with p130Cas in endothelial cells

Abstract: Membrane-type 1 matrix metalloproteinase (MT1-MMP) plays an important role in sphingosine-1-phosphate(S1P)-dependent migration of endothelial cells but the underlying mechanisms remain largely unknown. Herein, we show that S1P promotes the relocalization of MT1-MMP to peripheral actin-rich membrane ruffles that is coincident with its association with the adaptor protein p130Cas at the leading edge of migrating cells. Immunoprecipitation and confocal microscopy analyses suggest that this interaction required th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…Moreover, in MCF10A human breast epithelial cells, S1P induces secretion of MMP9 and migration via S1P3 and Gq/12 (Kim et al, 2011). Several other studies have shown that endothelial cell migration is enhanced by S1P via activation of MMP2 (Gingras et al, 2008;Wu et al, 2005). More importantly, MMP2 and MMP9 have been associated with enhanced invasion of thyroid cancer cells (Rajoria et al, 2011;Yang et al, 2013;Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, in MCF10A human breast epithelial cells, S1P induces secretion of MMP9 and migration via S1P3 and Gq/12 (Kim et al, 2011). Several other studies have shown that endothelial cell migration is enhanced by S1P via activation of MMP2 (Gingras et al, 2008;Wu et al, 2005). More importantly, MMP2 and MMP9 have been associated with enhanced invasion of thyroid cancer cells (Rajoria et al, 2011;Yang et al, 2013;Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…Matrix metalloproteinases are enzymes degrading the extracellular matrix and are widely accepted as inducers of cancer cell invasion and migration, as well as mediators of sphingolipid induced signaling events (Stamenkovic, 2000;Folgueras et al, 2004;Gingras et al, 2008;Sun et al, 2010;Wu et al, 2005;Devine et al, 2008). In order to find out whether S1P is able to regulate MMP2 and MMP9 in follicular ML-1 thyroid cancer cells, we treated the cells with 100 nM S1P for different times (2-6 h).…”
Section: S1p Induces Secretion and Activity Of Mmp2 And Mmp9mentioning
confidence: 99%
“…Previously, p130Cas (also known as BCAR1) has been shown to facilitate the interaction between MT1-MMP and FAK in tumor cells (Wang and McNiven, 2012). S1P enhances the interaction between p130Cas and pMT1-MMP Y573 in endothelial cells, although this interaction is predicted to be indirect because the cytoplasmic tail of MT1-MMP lacks binding motifs for SH2 or SH3 domains to facilitate interactions with tyrosine-phosphorylated proteins (Gingras et al, 2008). The present study suggests that pro-angiogenic factors enhance the formation of the complex between Hic-5 and MT1-MMP.…”
Section: Discussionmentioning
confidence: 99%
“…Although a specific proteinase was not identified, Hic-5 depletion has been connected to decreased matrix degradation and filopodia formation (Pignatelli et al, 2012). Wang and McNiven have previously implicated focal adhesions as sites for MT1-MMP-dependent matrix degradation in tumor cells (Wang and McNiven, 2012), and others have suggested the importance of MT1-MMP and focal adhesion crosstalk during cell migration (Wu et al, 2005b;Takino et al, 2006Takino et al, , 2007Gingras et al, 2008). Importantly, expression of the Hic-5 ΔLIM2-3 mutants that did not interact with MT1-MMP partially reduced invasion, despite the presence of endogenous Hic-5.…”
Section: Discussionmentioning
confidence: 99%
“…Whether such cooperative MT1-MMP to S1P signaling is physiologically relevant was further explored in alternate circulating cell models, such as T cells37 and bone marrow-derived mesenchymal stromal cells,38 where MT1-MMP functions were targeted by EGCG. Evidence possibly supporting such a cooperative MT1-MMP to S1P signaling axis was recently based on the fact that S1P induced the association of MT1-MMP with p130Cas in endothelial cells39 and that this interaction represents a novel mechanism in the macrophage cell fusion machinery 40…”
Section: Discussionmentioning
confidence: 99%